2023
DOI: 10.1001/jamanetworkopen.2022.55458
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Silver Diamine Fluoride on Caries Arrest and Prevention

Abstract: ImportanceDental caries is the most common global childhood disease. To control caries, the Centers for Disease Control and Prevention recommends school-based caries prevention, and the World Health Organization lists glass ionomer cement and silver diamine fluoride as essential medicines for oral disease.ObjectiveTo determine the noninferiority of silver diamine fluoride with fluoride varnish vs traditional glass ionomer sealants with fluoride varnish after 2 years when provided to children via a school-based… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
26
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 23 publications
(37 citation statements)
references
References 34 publications
1
26
0
2
Order By: Relevance
“…Our analysis used all available observations for study participants and also considered a subset of participants that had equal rates of follow-up to address the disruption in study activities due to the effects of COVID-19. Although prior results from CariedAway concluded that a single application of SDF and varnish was non-inferior to sealants/ART for caries arrest after two years, analysis was restricted to children who did not have dental caries at baseline 17 . The presented findings assessed non-inferiority inclusive of both children who did or did not begin the study with active untreated decay, which has previously not been reported.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Our analysis used all available observations for study participants and also considered a subset of participants that had equal rates of follow-up to address the disruption in study activities due to the effects of COVID-19. Although prior results from CariedAway concluded that a single application of SDF and varnish was non-inferior to sealants/ART for caries arrest after two years, analysis was restricted to children who did not have dental caries at baseline 17 . The presented findings assessed non-inferiority inclusive of both children who did or did not begin the study with active untreated decay, which has previously not been reported.…”
Section: Discussionmentioning
confidence: 99%
“…The trial was approved by the New York University School of Medicine Institutional Review Board (#i7-00578) and is registered at www.clinicaltrials.gov (#NCT03442309). A complete trial protocol is publicly-accessible 16 .…”
Section: Design and Participantsmentioning
confidence: 99%
See 1 more Smart Citation
“…School-based dental programs are effective and cost-efficient methods to increase access to care for vulnerable, traditionally underserved populations [17, 11, 18] and can significantly reduce the risk of disease [19, 20]. Closures of school-based health programs can exacerbate unmet needs in vulnerable populations.…”
Section: Discussionmentioning
confidence: 99%
“…School-Based Health Centers (SBHCs) increase access to critical health services for children [9], including primary and preventive medical care [10]. For oral health, the Centers for Disease Control and Prevention recommends school sealant programs [11], and other approaches to school-based dental care are similarly effective [12]. Closures of SBHCs and other school health programs to mitigate the spread of the pandemic meant that these vital services for children were inaccessible [13, 14].…”
Section: Introductionmentioning
confidence: 99%